A Threshold Disability Score Corresponds with an Estimated Diagnosis of Clinical Depression in Patients with Upper Extremity Disease. (June 2015) - Molleman, Jeroen; Janssen, Stein J.; Overbeek, Celeste L.; Ring, David
Background: The purpose of this study was to assess whether there is a threshold Disability of Arm, Shoulder and Hand (DASH) score among patients with common hand diagnoses that corresponds with an estimated diagnosis of clinical depression. Methods: Two hundred sixty-nine patients with one of five common upper extremity disorders completed a measure of upper extremity-specific disability (QuickDASH or DASH) and a questionnaire assessing depressive symptoms (Patient Health Questionnaire (PHQ) or Center for Epidemiologic Studies Depression scale (CES-D). A receiver operating characteristic (ROC) analysis of the discriminatory value of a threshold DASH score for an estimated diagnosis of clinical depression was assessed. The threshold DASH score with the highest positive predictive value for an estimated diagnosis of clinical depression was selected. In bivariate analysis, the association between demographic factors, disease factors, and an estimated diagnosis of clinical depression was examined. Results: The area under the ROC curve for a threshold DASH value diagnostic of an estimated diagnosis of clinical depression was 0.75, indicating clinical usefulness for a threshold DASH score as a screening test for depression. The highest positive predictive value of 72 % occurred at a threshold QuickDASH/DASH score of 55. In bivariate analysis, only diagnosis and years of education were significantly different between patients with and without an estimated diagnosis of clinical depression. Conclusion: A DASH score of 55 or greater in patients with common upper extremity disorders has an acceptable area under the curve and positive predictive value for an estimated diagnosis of clinical depression. Level of Evidence: Level 3, diagnostic study